Evaluation of six years of dental referrals from the pediatric inpatient area of Hospital Criança Conceição in Porto Alegre, Brazil - Márcia Cançado Figueiredo; Márcia Sesse-da Silva; Jacqueline Webster; Ximena Concha-Melgar; Daniel Demetrio Faustino-da Silva (Universidad de Antioquia, 2020)
Introduction: this study aimed to describe the profile of the referrals sent to the hospital dentistry team from patients in Hospital Criança Conceição in Porto Alegre, Rio Grande do Sul, Brazil, from January 2012 to July 2018. Methods: a descriptive, retrospective study was conducted, evaluating 193 electronic dental records to extract the following data: patient's sex and age, description of the referral made by other health professionals and the dentist's behavior in solving the presented problem. Results: 61.6% of patients were male and the mean age of all patients was 10.5 years. Most dental referrals came from the oncohematology area (75.12%) and the predominant reason was pre- and post-chemotherapy patients' dental care (40.4%). The diagnosis most commonly found by dentists was mucositis (17.6%) and caries (16%). There was absence of oral diseases in 23.8% of cases. The interventions most commonly performed by the hospital dentistry team were laser therapy (57.5%) and oral hygiene instructions (49.1%) in the hospital setting, while procedures in dental offices and surgical rooms included exodontias (27.7%) and restorations (11.7%). Conclusions: the profile of referrals sent to the hospital dentistry team from patients hospitalized in the Hospital Criança Conceição in Porto Alegre, Rio Grande do Sul, Brazil, is inadequate, since there was a lack of transdisciplinary management including dental care, in addition to poor use of information technology resources and lack of more objective medical records for easy retrieval of patient health information.